Miss Peregrine's Peculiar Children : The Desolations of Devil's Acre - Book 6 - Riggs, Ransom (New York : Dutton Books, 2021)
"The last thing Jacob Portman saw before the world went dark was a terrible, familiar face. Suddenly, he and Noor are back in the place where everything began--his grandfather's house. Jacob doesn't know how they escaped from V's loop to find themselves in Florida. But he does know one thing for certain: Caul has returned. Risen from the Library of Souls and more powerful than ever, Caul and his apocalyptic agenda seem unstoppable. Only one hope remains--deliver Noor to the meeting place of the seven prophesied ones. If they can decipher its secret location."--
Keywords: Paranormal fiction; Abnormalities, Human -- Juvenile fiction; Rescues -- Juvenile fiction; Time travel -- Juvenile fiction; Supernatural -- Fiction; Abnormalities, Human -- Fiction; Rescues -- Fiction; Time travel -- Fiction; England -- Juvenile fiction; England -- Fiction